(untitled) (Research, Society and Development, 2022)
This article aimed to analyze a list of highly cited Brazilian researchers linked to UNIFESP, through a comparison between the classification published by Elsevier and the citation counts provided by the databases Web of Science (Thomson Reuters), Scopus (Elsevier) and Google Scholar. Thus, it was possible to identify the similarities and differences between the databases and reflect on the metrics of scientific impact and productivity of researchers. The temporal space was defined by a five-year period, from 2016 to 2021. The research results were organized in tables, followed by the respective analyses and comparisons between the consulted databases. From the results obtained, there were divergences in the citation counts from one database to another, precisely because they use different sources for data compilation. Thus, knowing the characteristics of each of the available tools for citation search and its limitations can contribute to the choice of the best databases for calculating the H-index of researchers.